Assessing the Influence of Temperature‐Memory Creation on the Degradation of Copolyesterurethanes in Ultrathin Films. Issue 6 (1st February 2021) - Machatschek, Rainhard; Saretia, Shivam; Lendlein, Andreas
Abstract: Copolyesterurethanes (PDLCLs) based on oligo(ε‐caprolactone) (OCL) and oligo(ω‐pentadecalactone) (OPDL) segments are biodegradable thermoplastic temperature‐memory polymers. The temperature‐memory capability in these polymers with crystallizable control units is implemented by a thermomechanical programming process causing alterations in the crystallite arrangement and chain organization. These morphological changes can potentially affect degradation. Initial observations on the macroscopic level inspire the hypothesis that switching of the controlling units causes an accelerated degradation of the material, resulting in programmable degradation by sequential coupling of functions. Hence, detailed degradation studies on Langmuir films of a PDLCL with 40 wt% OPDL content are carried out under enzymatic catalysis. The temperature‐memory creation procedure is mimicked by compression at different temperatures. The evolution of the chain organization and mechanical properties during the degradation process is investigated by means of polarization‐modulated infrared reflection absorption spectroscopy, interfacial rheology and to some extend by X‐ray reflectivity. The experiments on PDLCL Langmuir films imply that degradability is not enhanced by thermal switching, as the former depends on the temperature during cold programming. Nevertheless, the thin film experiments show that the leaching of OCL segments does not induce further crystallization of the OPDL segments, which is beneficial for a controlled and predictable degradation. Abstract : Ultrathin films at the air water interface are manipulated in a controlled way to represent the semicrystalline morphology of a temperature‐memory polymer at distinct points of the programming/switching cycle. The degradability under enzymatic catalysis depends on the deformation temperature, which is also reflected in the viscoelastic properties throughout the entire degradation process.